1989
DOI: 10.1103/physrevlett.62.1193
|View full text |Cite
|
Sign up to set email alerts
|

Cu spin dynamics and superconducting precursor effects in planes aboveTcinYBa2

Abstract: Spin dynamics at planar sites in oxygen-deficient YBa2Cu306+x have been investigated by nuclear spin-lattice relaxation measurements using ^^'^^Cu nuclear quadrupole resonance and ^^Y NMR. A sharp decrease of ^^Cu nuclear relaxation below^ 100 K in YBaiCusOe? suggests the possible onset of spin pairing in individual planes well above the transition to three-dimensional bulk superconductivity. Comparison of the relaxation rates for the 60-K superconductor YBa2Cu306.7 with those of YBa2Cu307.o in the range 100-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
215
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(229 citation statements)
references
References 21 publications
14
215
0
Order By: Relevance
“…Some of these studies suggest that superconductivity persists even with no electron doping, [1][2][3] while others show presence of antiferromagnetic long range order in the lightly doped regime, 4,5) so that the issue is still controversial. It was also shown experimentally that the "pseudo gap", [6][7][8][9][10] a prominent feature of the cuprates, disappears if the antiferromagnetism is suppressed. 11) This is consistent with a theoretical study, which shows that the pseudo gap in the electron-doped case originates from the antiferromagnetism.…”
Section: Introductionmentioning
confidence: 93%
“…Some of these studies suggest that superconductivity persists even with no electron doping, [1][2][3] while others show presence of antiferromagnetic long range order in the lightly doped regime, 4,5) so that the issue is still controversial. It was also shown experimentally that the "pseudo gap", [6][7][8][9][10] a prominent feature of the cuprates, disappears if the antiferromagnetism is suppressed. 11) This is consistent with a theoretical study, which shows that the pseudo gap in the electron-doped case originates from the antiferromagnetism.…”
Section: Introductionmentioning
confidence: 93%
“…During that period, as I explained above, the only possible attitude for me was to stu ng publications through the "High T c update" abstracts archives channel, which was transformed later into the condmat archives sections. This is where I discovered that all NMR specialists were working quite naturally on 63 Cu NMR to get information on the SC properties. But I noticed a single work on 89 Y NMR, which revealed that, though out of the planes, this nucleus was still weakly coupled to the electronic properties of the planes and could be used to monitor them [50].…”
Section: The "Prehistormentioning
confidence: 99%
“…Measurements done in the group of A. Heeger (chemistry Nobel prize in 2000) revealed that the 63 Cu width increased below 30 K somewhat faster than expected from the high T CurieWeiss susceptibility, and saturated at low T [23]. This was initially taken as a signature of the development of a static polarized cloud anti-parallel to the local impurity magnetization.…”
Section: Spatial Extent Of the Kondo Singlet?mentioning
confidence: 99%
See 1 more Smart Citation
“…Transport experiments [14], ARPES [2,3], NMR [15,16], and optical conductivity [17,18] all detect a loss of spectral weight at low energies in the one-particle excitation spectrum below a certain temperature, T * > T c . Furthermore, the k-specific nature of the ARPES technique has shown that the pseudogap has nodes at the same places as the superconducting gap.…”
Section: Introductionmentioning
confidence: 99%